CEO's Operating Ability and the Association between Accruals and Future Cash Flows. (14th May 2015) - Choi, Wooseok; Han, Sam; Jung, Sung Hwan; Kang, Tony
Abstract This study investigates whether an individual CEO's operating ability, operationalized as the extent to which an individual CEO utilizes the company's assets efficiently to generate profits, explains the association between accruals and future cash flows. While this mapping can be driven by both the quality of accounting measurement and CEO operating ability, there is little empirical evidence on the latter link. After controlling for the CEO's accounting estimation ability, we find that the association between current period accruals and future cash flows is stronger when the CEO demonstrates superior operating ability. This suggests that a CEO's operating ability is an important determinant of the informativeness of current accruals for future cash flows.